Pengaruh Metode Outdoor Learning Berbantuan Media Benda Konkret Terhadap Hasil Belajar Matematika - Purwati Purwati; Tria Mardiana; Ita Kurniawati (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the affect of outdoor learning methods assisted by concrete objects media on the learning outcomes of mathematic students in grade V at SDN Kalisalak Salaman. This research method is Pre-experimental with a One Group Pretest-Postest Design. The subject was 19 students in grade V at SDN Kalisalak chosen by saturated sampling. The method of data completion is done by testing. Validity test of product-moment and reliability test using cronbach alpha formula by SPSS for Windows 25.0. The prerequisite test consists of a normality test by SPSS for Windows 25.0. Data analysis using parametric statistic technique that is Paired Sample T-Test by SPSS for Windows 25.0. The result shows that the outdoor learning method was assisted by concrete object media affected on learning outcomes of mathematic. This is evidenced by the results of the Paired Sample T-Test with a probability value of 0,000 < 0,05. Based on the results of the analysis and discussion, there are differences in the mean pretest 0f 58,95 and post-test of 87,89. Based on these studies it can be concluded that the application of the outdoor learning method assisted by concrete objects media affects the learning outcomes of mathematic.